El rol de las organizaciones sociales en asentamientos precarios - Mosso, Emilia Carla (Universidad Nacional del Litoral, 2014)
Recent changes evidenced in the territory, as a result of rapid changes, have been the subject of numerous research studies. The role of the state, private sector and civil society have had to redefine itself. New social organizations appear from the 80 decade as a new way to generate local interventions around specific topics and, in many cases, as managers of the formation and consolidation of neighborhoods, housing and urban habitat. This paper seeks to deepen understanding about urban precariousness in informal settlements in the city of Santa Fe, and investigate the role that social organizations acquire, particularly those changes that have occurred between the last decades of last century and the first of this one. It starts from the assumption that social organizations, taking a leading role by the absence of the role of the state, have become generators of profound changes in relation to urban habitat. Although very valuable investigations carried out so far, very few material is specifically referred to this problem, particularly in those areas affected by a marked process of urbanization such as Santa Fe.